Genetic deletion of Cav3.2 T-type calcium channels abolishes H2S-dependent somatic and visceral pain signaling in C57BL/6 mice - Kazuki Matsui; Maho Tsubota; Saaya Fukushi; Nene Koike; Hiroshi Masuda; Yoshihito Kasanami; Takaya Miyazaki; Fumiko Sekiguchi; Tsuyako Ohkubo; Shigeru Yoshida; Yutaro Mukai; Akira Oita; et al. (Journal of Pharmacological Sciences, 2019)
We tested whether genetic deletion of Cav3.2 T-type Ca2+ channels abolishes hydrogen sulfide (H2S)-mediated pain signals in mice. In Cav3.2-expressing HEK293 cells, Na2S, an H2S donor, at 100 μM clearly increased Ba2+ currents, as assessed by whole-cell patch-clamp recordings. In wild-type C57BL/6 mice, intraplantar and intracolonic administration of Na2S evoked mechanical allodynia and visceral nociceptive behavior, respectively, which were abolished by TTA-A2, a T-type Ca2+ channel blocker. In Cav3.2-knockout mice of a C57BL/6 background, Na2S caused neither somatic allodynia nor colonic nociception. Our study thus provides definitive evidence for an essential role of Cav3.2 in H2S-dependent somatic and colonic pain. Keywords: Hydrogen sulfide, Cav3.2 T-type calcium channel, Pain